Efektivitas Guru Pendamping dalam Proses Belajar Mengajar di TK Negeri Pembina Kota Tengah Kota Gorontalo - Rahmatia B. Salum; Yenti Juniarti; Sri Rawanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the effectiveness of assistant teachers in the teaching and learning process at TK Negeri Pembina, Kota Tengah, Gorontalo City. The research focuses include: (1) identifying the challenges faced by assistant teachers in the learning process, (2) understanding how the learning process is conducted by assistant teachers, and (3) evaluating the outcomes achieved in the implementation of the learning process by assistant teachers.The study employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The results indicate that assistant teachers play an active role in supporting classroom teachers, assisting and guiding children who require special attention. The tasks performed by assistant teachers reveal certain inconsistencies, such as assistant teachers taking on the role of classroom teachers. Despite challenges in managing students, asssistant teachers are able to contribute significantly to achieving learning objectives.